Investigation of friction stir spot welding of high density polyethylene and polypropylene sheets - BİLİCİ, MUSTAFA KEMAL (SAGE PUBLICATIONS LTD, 2021)
In this study, two different polymer materials were used. In the joints made with friction stir spot welding, firstly (PP/PP and HDPE/HDPE) and then different materials (PP/HDPE, HDPE/PP) joining processes were carried. The influence of the tool rotational speed and the stirring time on joint formation and weld strength were determined. The temperature of the liquid welding materials varies according to the materials to be combined. High weld strengths were obtained at the friction stir spot welding of similar plastic sheets. The highest weld strengths were obtained in PP-PP welds. Low weld strengths were obtained at the friction stir spot welding of dissimilar plastic sheets because of immiscible and incompatible blends formed during the welding operation. The lowest weld strengths were obtained in PP-HDPE welds. The chemical composition and the phase morphology of the blends, the mechanical scission occurrence and the welding residual stresses determine the strength of the welds.
Keywords: Friction stir spot welding; processing technologies; industrial applications; mechanical properties; polymer welding